If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + x = 8x Solving 36 + x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 36 + x + -8x = 8x + -8x Combine like terms: x + -8x = -7x 36 + -7x = 8x + -8x Combine like terms: 8x + -8x = 0 36 + -7x = 0 Add '-36' to each side of the equation. 36 + -36 + -7x = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -7x = 0 + -36 -7x = 0 + -36 Combine like terms: 0 + -36 = -36 -7x = -36 Divide each side by '-7'. x = 5.142857143 Simplifying x = 5.142857143
| 4-a=-4 | | 3x+6+8x=47 | | C-0.12m(500)=330 | | -3=3x+0 | | C-0.12(500)=33 | | 5x+9x+2=22 | | 3(x-7)3-11=13 | | -2.9=1.1 | | 567-540= | | 15-20x=-585 | | 6g+4(-6+2g)=1-g | | ln(y+1)+ln(y-1)=1 | | 6g+4(6+2g)=1-g | | 6x+1+11x+2=44 | | -6(4x-7)=-24x-42 | | 4p-4=p+4 | | 2(3+5x)=86 | | 4p-4=p | | 10a-14=286 | | (3y-5)+(5y+20)=-22 | | y-15=2(x-6) | | 89+3=21 | | X+8+2x-1=11 | | 18=8(u-3)-2u | | (5m-10)(m+4)=0 | | -6=2x+2(x+3) | | c(200)=6.2x+10100 | | 15+12/2= | | X+8=76 | | -10n+4=-86 | | (5+7i)(4-12i)= | | -11x+12=-7x |